The Repercussion of COVID-19 on U.S Hegemony: Recession or Expansion - بن عيشة, كنيوة, هاجر شيماء (University of El-oued, 2022)
منذ أن طرق كوفيد-19 أبواب العالم في منتصف القرن الحادي والعشرين، اختلفت استراتيجيات هيمنة الولايات المتحدة تجاه الوباء من دولة إلى أخرى ومن رئيس إلى آخر. تحاول هذه الدراسة توضيح العوامل التي جعلت الولايات المتحدة تهيمن وتلقي الضوء على تداعيات كوفيد-19 على الهيمنة الأمريكية. تهدف أيضًا إلى التحقيق في الاستراتيجيات والممارسات السياسية لإدارة بايدن وترامب ، من 2019 إلى 2022 وتأثيرها على هيمنة الولايات المتحدة. والمنهج المتبع لتحقيق هذا الغرض هو منهج وصفي تحليلي ، حيث تهدف الدراسة إلى وصف صعود الهيمنة الأمريكية وتحليل تأثير الاستراتيجيات والممارسات السياسية التي اعتمدتها الإدارتان. تظهر النتائج التي تم الحصول عليها من الدراسة أن هيمنة الولايات المتحدة متأثرة بجائحة كوفيد-19 وأن ممارسات إدارتي بايدن وترامب لا تبذل جهودًا كافية وجميع المبادرات التي طرحتها لا تمنح هيمنة الولايات المتحدة فرصة لاستعادة الركود الناجم عن كوفيد-19 الحالي. Since COVID-19 knocks the door of the world in the mid 21th century, the strategies of Unites States hegemony toward the pandemic varied from one country to another and from one president to another. This study attempts to clarify the factors that made United States hegemony and casts light on the repercussion of COVID-19 on U.S hegemony. Also aims at investigating the political strategies and practices of the Biden and Trump's administration, from 2019 to 2022 and their impact on the United States hegemony. The method adopted to achieve this purpose is a descriptive-analytical method, where the study intends to describe the rise of the United States hegemony and to analyze the impact of the political strategies and practices adopted by the two administrations. The results obtained from the study demonstrate that the United States hegemony is influenced by COVID-19 pandemic and the practices of the two administrations of Biden and Trump do not give enough efforts and all the initiatives put forward by them do not give the United States hegemony a chance to recapitulate the recession caused by the current COVID-19.
Keywords: السياسة, الولايات المتحدة, القوة, الهيمنة، كوفيد-19; Hegemony, COVID-19, U.S,politics, power